The Notorious Bettie Page - Harron, Mary; Hupfel, Mott; Mol, Gretchen; Bauer, Chris; Harris, Jared (Icon Film, 2007)
The idea that images have power was a revelation to Bettie Page. In Mary Harron's precisely rendered portrait of the Christian girl from Nashville who became one of America's most famous pin-up queens, our somewhat naïve heroine is slow to realize what the sight of her does to men. The attention is often not good: early scenes include harrowing glimpses of Page's victimization by her father, her first husband and a predatory posse of local boys. Yet Harron deftly shows how Bettie discovers herself through her dalliances with the camera. She relishes the safety and confidence she finds in front of the lens, whether she's posing for "camera clubs" full of grubby-fingered amateurs or doing more outré bondage scenarios in the studio run by Irving Klaw and his sister Paula. The stylistic echoes of Sirk, Fuller and Fassbinder help "The Notorious Bettie Page" tweak the biopic formula, as does Harron's careful consideration of questions about censorship, sexual representation and what happens when a woman is turned into an object of desire. Gretchen Mol's performance brilliantly conveys both Page's unfettered joy when on display and her wariness once she realizes she's gotten in way over her pretty little head. While the film's tone is more coolly analytical than its va-va-voom subject would promise, Mol makes sure her Page is taken seriously even when her clothes are off. [www.eyeweekly.com]
Keywords: DVD-Video